Consensus statements among European sleep surgery experts on tongue, hypopharynx, and supraglottis associated with snoring and obstructive sleep apnea: part 1: Evaluation and decision making - Olszewska, Ewa; Vito, Andrea De; Baptista, Peter; Delakorda, Matej; Heiser, Clemens; Cheong, Ryan C. T.; Plaza, Guillermo; Vanderveken, Olivier; Pérez-Martin, Nuria; Kotecha, Bhik; Maurer, Joachim T.; Vicini, Claudio (Journal of Clinical Medicine, 2025)
The tongue base, hypopharynx, and supraglottis (TngHpxSgl) play distinct roles in snoring and obstructive sleep apnea (OSA). Aim of the Study: To assess the level of consensus on the assessment and decision-making for the management of snoring and OSA associated with TngHpxSgl. Methods: A set of statements on the assessment and decision-making for the management of snoring and OSA associated with TngHpxSgl was developed based on the literature and circulated among 12-panel members of European experts on sleep surgery, using the modified Delphi method, seeking at least 80% consensus. Responses were categorized as agree or disagree for each statement, and the comments from the panelists were used to assess the level of consensus. Statements containing aggregated anonymized responses and comments were sent to each panel member in the second and final rounds of the survey. Results: The final set included 147 statements. Of these, 52.6%, 14.7%, and 5.8% achieved consensus among all 12, 11, and 10 panelists, respectively. Conclusions: There was a high level of consensus (73.2%) among European sleep surgery experts on the statements. This consensus will help establish standards and guide further research on snoring and OSA related to TngHpxSgl.
Gesehen am 19.02.2026